2016
DOI: 10.1097/md.0000000000002247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Foot Pump on the Incidence of Deep Vein Thrombosis After Total Knee Arthroplasty in Patients Given Edoxaban

Abstract: We conducted a randomized clinical trial to compare the effectiveness of the A-V Impulse System foot pump for reducing the incidence of deep-vein thrombosis (DVT) after total knee arthroplasty (TKA) in patients under edoxaban thromboprophylaxis.Patients undergoing primary TKA at our institution between September 2013 and March 2015 were enrolled after obtaining informed consent. The patients were randomized to use the foot pump (n = 58) and not to use the foot pump (n = 62). Both groups were given prophylactic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…[23][24][25][26]28,29,[31][32][33] We identified 19 studies in these reviews that fulfilled our inclusion criteria and measured outcomes relevant to this context. 36,60,62,68,70,[104][105][106][107][108][109][110][111][112][113][114][115][116][117] Our systematic search of RCTs did not identify any additional study that fulfilled the inclusion criteria.…”
Section: Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26]28,29,[31][32][33] We identified 19 studies in these reviews that fulfilled our inclusion criteria and measured outcomes relevant to this context. 36,60,62,68,70,[104][105][106][107][108][109][110][111][112][113][114][115][116][117] Our systematic search of RCTs did not identify any additional study that fulfilled the inclusion criteria.…”
Section: Recommendationmentioning
confidence: 99%
“…36,60,62,68,104,105,107 Ten studies reported the effect on the development of symptomatic PEs, 60,62,68,70,105,107,[109][110][111]117 and 6 studies reported the effect on any PE. 36,104,108,112,116,117 Three studies reported data on symptomatic proximal DVTs, 62,70,112 and 8 studies reported data on any proximal DVT. 62,70,104,108,[112][113][114] Three studies reported data on symptomatic distal DVTs, 70,105,112 and 7 studies reported on any distal DVT.…”
Section: Recommendationmentioning
confidence: 99%
“…Edoxaban resulted more efficient in comparison to the other two prophylaxis regimens. A randomized study evaluated the effectiveness of a A-V Impulse System foot pump associated with edoxaban in the prophylaxis of DVT after TKA [51]. The authors did not find any significant difference in primary outcomes (any DVT as detected by bilateral ultrasonography up to postoperative day 10 and pulmonary embolism PE up to postoperative day 28 ) and safety outcomes ( bleeding and death of any cause up to postoperative day 28).…”
Section: Edoxabanmentioning
confidence: 96%
“…Although there was no significant difference in the incidence of DVTs between the 2 groups (P = 0.089), the incidence of postoperative DVTs were higher in patients with the use of the foot pump (31.0%) compared to those without use of foot pump (17.7%). Modified form of figure in the article by Sakai T, et al 19) . 24) .…”
Section: Vte and Seroconversion Rate Of Anti -Pf4/heparin Antibodies mentioning
confidence: 99%
“…These data suggested that the use of mechani cal devices including foot pump, either alone or in combination with chemical thromboprophylaxis did not reduce the rate of VTE. Sakai et al conducted a randomized clinical trial to compare the effectiveness of foot pump use for reducing the incidence of DVT after TKA in patients under edoxaban thromboprophylaxis 19) . As shown in Figure 2, the incidence of all DVTs in patients using a foot pump was 31.0% (18/58) compared with 17.7% (11/62) in patients not using a foot pump.…”
Section: Incidence Of Vte In Patients Receiving Arthroplastymentioning
confidence: 99%